The West and the Third World - O'Neill, Robert. author. aut Link
XII, 305 p.
Keywords: This is a book of essays in honour of J.D.B.Miller and looks at the relationship between the West and the Third World. It looks especially at the liberal/democratic West in opposition to the communist East and that version of modernity which is represented by the developed capitalist world.